Transparency in design. - Staples, Loretta (International Review of African American Art, 1996)
Focuses on the issue of transparency in software and interface design. Transparency as a natural, `noise-free' dynamic between object and user; Author's claim of tools as relatively content-free; Entry of the concept of `affordables' into design vocabulary. INSET: Sound bite, by Noel Mayo..